G‐Factor, a Suitable Tool for Characterization of Ancient Ceramics: Application to Monitoring Amphorae Phase Transformations in Firing. (20th May 2014) - Compana, J. M.; Cabeza, A.; Macias, J.; Aranda, M. A. G.; León‐Reina, L.
Abstract : The thick Pliocene clay beds located along the mouth of the Guadalhorce River in Malaga were used in the Roman era for amphorae production related to the ever‐growing production of garum and salted fish. As a first step in their archaeometric characterization, a series of firing tests on the potential raw material have been carried out. The main aim of this work is to obtain a suitable tool for estimating the firing temperatures of those amphorae, as well as to make a comprehensive evaluation of the potential of an innovative external‐standard method for measuring the amorphous content of a pottery sample, the G‐factor method. The obtained results emphasize a highly amorphous content, over 50 wt% in some samples, which varies with the firing temperature. This shows the potential of this technique, which allows straightforward fully quantitative mineralogical analysis and a mineralogical comparison even between samples fired at very different temperatures.